Development of a multi-objective scheduling system for offshore projects based on hybrid non-dominated sorting genetic algorithm. (18th March 2015) - Li, Jinghua; Yang, Boxin; Zhang, Dan; Zhou, Qinghua; Li, Lingyao
In order to enhance the efficiency of offshore companies, a multi-objective scheduling system based on hybrid non-dominated sorting genetic algorithm was proposed. An optimized model for multi-objective and multi-execution mode was constructed under the condition of taking time, cost, and resource into account, and then the mathematical model for the same was established. Moreover, the key techniques of the proposed system were elaborated, and the flowchart was designed. Aiming at the weaknesses of non-dominated sorting genetic algorithm which is short for non-dominated sorting genetic algorithm-II in the facet of local search and computational efficiency, Pareto-dominated simulated annealing algorithm was applied in search global solution. Finally, by simulation examples and industrial application, the robustness and outperformance of the improved algorithm were verified.